2017
DOI: 10.5606/ehc.2017.55186
|View full text |Cite
|
Sign up to set email alerts
|

Does leukocyte-poor or leukocyte-rich platelet-rich plasma applied with biopolymers have superiority to conventional platelet-rich plasma applications on chondrocyte proliferation?

Abstract: ÖZAmaç: Bu çalışmada trombositten zengin plazma (TZP) içeriğindeki lökosit konsantrasyonunun ve TZP'nin ilaç taşıyıcı sistem kullanılarak uygulanmasının in vitro koşullarda kondrosit proliferasyonu üzerine olası etkileri araştırıldı. Hastalar ve yöntemler: Medikal veya konservatif tedaviye yanıt vermemiş ve total diz artroplastisi geçirmiş dokuz erkek hastanın (ort. yaş 65 yıl; dağılım 49-81 yıl) kanı iki formülasyon hazırlamak üzere kullanıldı: Düşük konsantrasyon lökositli TZP (2000-4000 lökosit/µL) saf TZP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…As SSEA-1 is a marker for chondrocytic differentiation (13), no further morphological experiments, including flow cytometry or Giemsa staining were performed. Previous studies have also demonstrated that ESEM analysis reveals morphological abberations (10,13,37). …”
Section: Discussionmentioning
confidence: 87%
“…As SSEA-1 is a marker for chondrocytic differentiation (13), no further morphological experiments, including flow cytometry or Giemsa staining were performed. Previous studies have also demonstrated that ESEM analysis reveals morphological abberations (10,13,37). …”
Section: Discussionmentioning
confidence: 87%
“…We believe that during centrifugation the denser granulocytes tend to stay trapped in the red cell layer of the centrifugate and thus are not captured in the PRP. This is significant for PRP prepared by single-spin methods because it shows that at least part of the controversy over whether leukocyte-rich (LRPRP) or leukocyte-poor (LPPRP) PRP [9][10][11] is clinically better for therapeutic purposes may be due to differences in leukocyte types rather than just leukocyte quantities. Few head-to-head trials have been performed comparing LRPRP and LPPRP, and no definitive conclusions can be drawn at this point.…”
Section: Discussionmentioning
confidence: 99%
“…Most cytotoxicity studies used experimental setups involving tissues of living mammalian subjects (16,17). However, the results obtained with animal tissues may be different from those obtained with human tissue due to differences in sensitivity (18). In numerous studies where animal tissues were not used, commercial cell lines were used (19,20).…”
Section: Discussionmentioning
confidence: 99%